Orthodontic Management of Maxillary Canine-first Premolar Transposition by Unilateral Extraction - Adiwirya, Muhammad Sulaiman Kusumah; Purwanegara, Miesje Karmiati (UI Scholars Hub, 2019)
Introduction: Transposition is an extreme and unique form of ectopic eruption. Orthodontic correction of transposed teeth in permanent dentition comprises the following treatment options: teeth alignment in the transposed position, orthodontic tooth movement into correct teeth order, or extraction on one of the transposed teeth followed by orthodontic correction. Case report: A 20-years-old male presented severe crowding and dental midline shift on both arches, followed by complete transposition of maxillary left canine – first premolar. A supernumerary tooth was also revealed between maxillary lateral and first premolar on the left side. The patient was treated with a pre-adjusted edgewise fixed appliance system. Extraction of supernumerary tooth and unilateral first premolars on the left side were performed to relieve crowding and to achieve stable occlusion. Improvement of smile aesthetic, correction of midline shift, and also an ideal class I of canine and posterior interdigitation were achieved after 22 months of treatment. Conclusion: Definitive treatment of transposition depends on the occlusion, degree of crowding, aesthetics, root position of the transposed teeth, and specific needs of the patient. Care must be taken to prevent midline shift and development of arch asymmetry during orthodontic correction of transposition involving unilateral extraction.